Nanostructured Biomaterials designed for chondral tissue engineering - Lastra, María Laura (2017)
The hypothesis of the present work is that the imitation of the extracellular matrix (ECM) using nanostructured materials based on natural polymers could restore the damaged osteochondral tissue. To prove our hypothesis we designed nanostructured matrices based on fumaric copolymer (diisopropyl fumarate-vinyl acetate copolymer) and chitosan crosslinked with borax, using anodized aluminum oxide (AAO) templates of two different pore diameter (170 nm and 300 nm). The obtained nanorods presented a highly homogenous diameter and length pattern as demonstrated by SEM.